(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
India and Bangladesh share not only close historical, civilisational and cultural links but have also forged strong political ties over decades since Bangladesh’s liberation in 1971. United by a shared history and common heritage, linguistic and cultural links, fervour for arts, music and literature, and strong people-to-people ties, the two countries share a unique camaraderie and friendship. Bangladesh and India commemorated their historic 50-year partnership. The two nations’ connection has been described as "a multidimensional fraternal relationship," persevering over the course of the previous fifty years despite a number of difficulties. The scope of their collaboration has been rising. This paper reflects status of Political Relation between India Bangladesh.